Peran Influencer Dalam Belanja Online Di Media Sosial TikTok - Rafael Danendra; Kevin Kennedy; Allvine Christian; Marogunawan Marogunawan (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This journal explains how much interest the general public has in shopping online, especially via TikTok. In this journal we also use a qualitative approach method. We use this approach because it has its own relevance in this journal. The choice of TikTok in this research is because TikTok is a social media with quite a large number of users in Indonesia. This is the benchmark for our research. How impactful are TikTok influencers in influencing the opinions of buyers and potential buyers, whether they will have an impact on purchasing power or not